2014
DOI: 10.7314/apjcp.2014.15.10.4217
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiles of Peripheral Blood Leukocytes Identify Patients with Cholangiocarcinoma and Predict Outcome

Abstract: Cholangiocarcinoma (CCA), a slow growing but highly metastatic tumor, is highly prevalent in Northeast Thailand. Specific tests that predict prognosis of CCA remain elusive. The present study was designed to investigate whether peripheral blood leukocyte (PBL) transcriptional profiles might be of use as a prognostic test in CCA patients. Gene expression profiles of PBLs from 9 CCA and 8 healthy subjects were conducted using the Affymetrix HG_U133 Plus 2.0 GeneChip. We indentified informative PBLs gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Here, high expression of PAI-2 was observed and correlated with poor prognosis in CCA patients. PAI-2, previously detected in peripheral blood lymphocytes of CCA patients was proposed as part of a set of markers of independent and statistically significant predictors of patient survival [ 40 ]. We suggest that in addition to lymphocytes, cancer cells and CCFs may be additional sources of PAI-2 released into the microenvironment of CCA tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Here, high expression of PAI-2 was observed and correlated with poor prognosis in CCA patients. PAI-2, previously detected in peripheral blood lymphocytes of CCA patients was proposed as part of a set of markers of independent and statistically significant predictors of patient survival [ 40 ]. We suggest that in addition to lymphocytes, cancer cells and CCFs may be additional sources of PAI-2 released into the microenvironment of CCA tissues.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines have been reported to support the transformation of cells into malignancy and invasiveness . Clinical study investigating peripheral blood leukocyte transcriptional profiles has identified IL‐8 as one of the disease predictive genes for cholangiocarcinoma . Interestingly, the expression of IL‐8 and IL‐6 in isolated cholangiocytes as well as serum level of IL‐8 is proved to be increased in the patients with primary sclerosing cholangitis, which carries a particularly high risk for the development of cholangiocarcinoma with prevalence between 5 and 15% .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high infiltration of M2 macrophages in tumor tissues is associated with poor clinical prognosis. [28] Given the tumor-supporting role of TAMs, there is significant interest in reprogramming TAMs from tumorpromoting to tumor-suppressing cells. [29]…”
Section: Immune Cellsmentioning
confidence: 99%